Screen, Ration and Churn: Demand Management and the Crisis in Children's Social Care. (10th April 2019) - Hood, Rick; Goldacre, Allie; Gorin, Sarah; Bywaters, Paul
Abstract: This article presents findings from a quantitative study of the national data-sets for statutory children's social care services in England. The aim of the study was to examine how demand management varied in local authorities with differing levels of area deprivation. About 152 local authorities census returns and other statistical indicators covering the period 2014–2017 were combined into a single data-set. Statistical analysis was undertaken to explore trends over time and correlations between indicators that might indicate patterns in the way demand was managed. Findings showed that high levels of deprivation have continued to be strongly linked to high levels of activity and that local authorities have continued to increase their use of protective interventions relative to referrals. Evidence was found for three interconnected mechanisms, through which local authorities tended to manage demand for services: screening, rationing and workforce churn. The article describes these mechanisms and comments on their significance for the current crisis of demand in the sector.